Evaluation parameters of a university library activity in the context of its tasks changes - E. N. Opekunova (Библиосфера, 2017)
The article describes challenges facing university libraries in different historical periods, identifies the most stable prior areas to form a system of indicators. It shows that a university library as a part of a higher education establishment environ acts as an element of the education system and changes in accordance with trends of its information space development, changing the orientation vector, when performing tasks, maintaining original functions (educational, culturaleducational, scientific-informational, social ones). The conclusions suggest that the indicators system to evaluate a university library activity should reflect completeness and availability of a library collection, customer orientation in library-information services, as well as an economic efficiency of library resources costs.